Individual hemoglobin mass response to normobaric and hypobaric "live high-train low": A one-year crossover study - Hauser, A.; Troesch, S.; Saugy, J. J.; Schmitt, L.; Cejuela-Anta, R.; Faiss, R.; Steiner, T.; Robinson, N.; Millet, G. P.; Wehrlin, J. P. (Journal of Applied Physiology, 2017)
The purpose of this research was to compare individual hemoglobin mass (Hbmass) changes following a live high-train low (LHTL) altitude training camp under either normobaric hypoxia (NH) or hypobaric hypoxia (HH) conditions in endurance athletes. In a crossover design with a one-year washout, 15 male triathletes randomly performed two 18-day LHTL training camps in either HH or NH. All athletes slept at 2,250 meters and trained at altitudes <1,200 meters. Hbmass was measured in duplicate with the optimized carbon monoxide rebreathing method before (pre) and immediately after (post) each 18-day training camp. Hbmass increased similarly in HH (916-957 g, 4.5 ± 2.2%, P < 0.001) and in NH (918-953 g, 3.8 ± 2.6%, P < 0.001). Hbmass changes did not differ between HH and NH (P = 0.42). There was substantial interindividual variability among subjects to both interventions (i.e., individual responsiveness or the individual variation in the response to an intervention free of technical noise): 0.9% in HH and 1.7% in NH. However, a correlation between intraindividual delta Hbmass changes (%) in HH and in NH (r = 0.52, P = 0.048) was observed. HH and NH evoked similar mean Hbmass increases following LHTL. Among the mean Hbmass changes, there was a notable variation in individual Hbmass response that tended to be reproducible.